O brother, where art thou? - Coen, Joel.; Coen, Ethan; Clooney, George; Turturro, John, 1957-; Nelson, Tim Blake; Durning, Charles, 1923-2012; Goodman, John, 1952-; Hunter, Holly, 1958-; Homer; Touchstone Pictures; Universal Pictures Corporation; Studio Canal+.; et al. (Burbank, Calif. : Touchstone Home Video : distributed by Buena Vista Home Entertainment, 2001)
Loosely based on Homer's "Odyssey", this is the story of three convicts-- escapees from a prison farm in Mississippi-- and their adventure as they travel home in hopes of recovering buried loot before it's lost forever in a flood.
Originally released as a motion picture in 2000.
Special features: Behind-the-scenes featurette; Painting with pixels, the groundbreaking digital production process; script to storyboard to final scene comparisons; I am a man of constant sorrow, music video; animated menus; theatrical trailer.
Director of photography, Roger Deakins ; editors, Roderick Jaynes, Tricia Cooke ; music, T. Bone Burnett.
George Clooney, John Turturro, Tim Blake Nelson, Charles Durning, John Goodman, Michael Badalucco, Holly Hunter.
MPAA rating: PC-13; for some violence and language.
DVD; NTSC, region 1; widescreen (2.35:1); Dolby Digital 5.1 surround sound.
Keywords: Escapes -- Drama; Redemption -- Drama; Depressions -- 1929 -- United States -- Drama; Comedy films; Feature films; Video recordings for the hearing impaired